PROGRAM PELATIHAN DASAR CALON PEGAWAI NEGERI SIPIL PADA PUSAT PELATIHAN DAN PENGEMBANGAN DAN KAJIAN MANAJEMEN PEMERINTAHAN LEMBAGA ADMINISTRASI NEGARA KOTA MAKASSAR - Wandira, Rezky Surya; Fatmawati, Fatmawati; Andriana, Andriana (Universitas Muhammadiyah Makassar, 2023)
This research is to find out how to process the stages and analyze the Basic Training Program for Civil Servant Candidates at the Center for Training and Development and Government Management Studies. The type of this research is descriptive qualitative research which is sourced from the data using purposive, sampling technique. The results showed that the implementation of basic training for CPNS at Puslatbang KMP LAN RI Makassar City from the aspect of 1) Effectiveness, namely the facilities and infrastructure that had been effectively carried out seen from the evaluation responses of the participant respondents, namely the results of the effectiveness, namely 94.55% had been effective and the next effectiveness was The material provided to the training participants provides maximum results. 2) Accuracy, namely the methods and methods used in this training there are 2, namely classical and blended learning and 3) Responsiveness, namely the facilitator's strategy to teach the results of the basic cpns training agenda. In terms of facilities and infrastructure, materials, and methods can be said to be effective. Where all indicators are very positive and motivating during the implementation of basic CPNS training.